McGlue - Moshfegh, Ottessa 1981- (Penguin Books, 2019)
Salem, Massachusetts, 1851: McGlue is in the hold, still too drunk to be sure of name or situation or orientation--he may have killed a man. That man may have been his best friend. Intolerable memory accompanies sobriety. A-sail on the high seas of literary tradition, Ottessa Moshfegh gives us a nasty heartless blackguard on a knife-sharp voyage through the fogs of recollection
"First published in the United States by Fence Books 2014.
Keywords: Detective and mystery stories; FICTION / Crime; FICTION / Historical; FICTION / Literary; Detective and mystery fiction; Thrillers (Fiction); Suspense fiction; Mystery fiction